The influence of cognitive abilities and anxiety on academic achievement among 10 and 11 year old children in elementary school - Ásta Björg Magnúsdóttir 1989- (2013)
An important topic in psychology is the prediction of academic achievement. Studies have shown that there are many different psychological and cognitive components that influence academic achievement. Cognitive ability tests that measure verbal comprehension, spatial ability, working memory span and more have been shown to relate to different skills in the academic environment. Anxiety is another component that has been shown to correlate strongly with academic achievement and especially on scores on mathematical exams. The main aim of the present study is to examine how well cognitive tests and anxiety predict performance on exams measured at different time intervals. Participants were 67 children (28 males and 39 females) at the age of 10 to 11 from an elementary school in Iceland called Hofsstaðaskóli. Participants were measured on four cognitive tests, two tests from Wechsler Intelligence Scale for Children (WISC), Raven‘s progressive matrices and Operation Span Task (OSPAN). Anxiety measures were questions that participants answered at three different time intervals. According to the results, the best predictors of scores on mathematics exams was OSPAN task and the best predictor for Icelandic exams was a WISC similarity test. Anxiety was the best predictor of scores on a mathematics exam from the spring of 2012.